ISOLATION, IDENTIFICATION, AND PATHOGENICITY OF SP. CAUSING STEM ROT IN DRAGON FRUIT (Journal of Plant Disease Sciences, 2025)
Dragon fruit is an emerging high-value crop in tropical and subtropical regions, affected by stem rot disease, posing a significant threat to its commercial cultivation. The present study was undertaken during 2023–2024 at ICAR–National Institute of Abiotic Stress Management (NIASM), Baramati, to isolate, identify, and assess the pathogenicity of Fusarium spp. associated with stem rot in dragon fruit. Disease samples exhibiting typical necrotic lesions were collected from ICAR-NIASM orchards and nearby farmer fields. Pathogen isolation was performed on potato dextrose agar (PDA), resulting in pure cultures from 20 out of 25 samples. Eight distinct isolates were characterized based on cultural and morphological features, including colony pigmentation, hyphal structures, and conidial measurements. Macroconidia were typically 3–5 septate, slender, and foot-shaped at the basal cell, while microconidia were oval to spindle-shaped and 0–2 septate; chlamydospores were observed in select isolates. Pathogenicity was confirmed via a detached cladode assay under controlled laboratory conditions using a standardized spore suspension (1×10⁶ spores/mL). Inoculated cladodes developed characteristic stem rot symptoms, and the pathogen was successfully re-isolated, fulfilling Koch's postulates. The findings confirm Fusarium oxysporum and F. solani as key causal agents of stem rot in dragon fruit. This study provides foundational data for targeted disease management strategies and contributes to sustainable dragon fruit production in India.
Keywords: Dragon fruit; Fusarium spp; Identification; Pathogenicity